1997
DOI: 10.1063/1.119415
|View full text |Cite
|
Sign up to set email alerts
|

Ionized donor bound excitons in GaN

Abstract: The temperature and excitation power dependence of a bound exciton photoluminescence line S with a localization energy Q=11.5 meV has been studied in undoped and moderately Mg-doped wurtzite GaN of high resistivity. The data provide strong evidence that line S is due to recombination of excitons bound to ionized shallow donors. The consistency of this assignment with theoretical predictions is demonstrated

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
31
1

Year Published

1998
1998
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(38 citation statements)
references
References 13 publications
6
31
1
Order By: Relevance
“…The deeper localized center DBX3 (E loc = 13±2 meV) exhibits a larger E act of 8.0±0.1 meV which describes the more rapid thermalization of DBX3. A similar thermalization behavior for DBX2 and DBX3 has been observed byŠantic et al 56 in nominally undoped and moderately Mg doped (4 × 10 17 cm −3 − 2 × 10 18 cm −3 ) GaN and suggests the attribution of DBX3 to the ionized donor bound exciton D + X which directly corresponds to the neutral state DBX2 (D 0 X). Interestingly, we observe an opposite scaling of E act for ABX1-3 over the corresponding E loc (Tab.…”
Section: Determination Of the Activation Energiessupporting
confidence: 50%
See 2 more Smart Citations
“…The deeper localized center DBX3 (E loc = 13±2 meV) exhibits a larger E act of 8.0±0.1 meV which describes the more rapid thermalization of DBX3. A similar thermalization behavior for DBX2 and DBX3 has been observed byŠantic et al 56 in nominally undoped and moderately Mg doped (4 × 10 17 cm −3 − 2 × 10 18 cm −3 ) GaN and suggests the attribution of DBX3 to the ionized donor bound exciton D + X which directly corresponds to the neutral state DBX2 (D 0 X). Interestingly, we observe an opposite scaling of E act for ABX1-3 over the corresponding E loc (Tab.…”
Section: Determination Of the Activation Energiessupporting
confidence: 50%
“…Fig. 7a exhibits a rather fast thermalization behavior of DBX3 (E act = 8.0±0.1 meV) in comparison to DBX2 (E act = 7.3±0.4 meV) which has also been observed byŠantic et al 56 in nominally undoped and moderately Mg doped (4 × 10 17 cm −3 − 2 × 10 18 cm −3 ) GaN. This allows the assignment of DBX3 to a D + X which corresponds to the neutral bound exciton state DBX2 (D 0 X).…”
supporting
confidence: 59%
See 1 more Smart Citation
“…It has been suggested that the I X emission is due to the exciton bound to the ionized donor. 6,7 The (D + ,X) complex is more stable in systems with a smaller ratio of the electron and hole effective mass σ = m e /m h . 14 Maintaining the hole bound to the donor is the weak link in the stability of the (D + ,X) complex.…”
Section: Figure 2 Temperature Dependence Of the Integrated Pl Intensmentioning
confidence: 99%
“…This emission has been identified as a neutral acceptor-bound exciton (A 0 ,X) 3,4 or a neutral donor-bound exciton (D 0 ,X) 5 and more recently was assigned to an ionized donor-bound exciton (D + ,X). 6,7 The identification of the various emissions in GaN is essential to understanding and improving device performance via better dopants and more efficient luminescence.…”
Section: Introductionmentioning
confidence: 99%